ANALISIS KELAYAKAN USAHA “UD LESTARI” DI DESA GUMUK KECAMATAN PANARUKANKABUPATEN SITUBONDO - Anik Sudarismiati; Siti Yuliyana (Growth, 2019)
This study aims to determine the business feasibility of UD. LESTARI Gumuk Village RT 06 Panarukan Subdistrict Situbondo Regency. If viewed from several investment valuation methods, namely the Payback Period (PP) method, the average rate of return (ARR) method, the Net Present Value (NPV) method, the Profitability Index (PI) method, and Internal Rate Of Return (IRR) method. The method of data collection is done by interview and observation. The data analysis method used is the analysis of the payback period (PP) results of 0.9 years or 9 months shorter than the maximum payback period of the business, which is for 2 years, then the proposed business investment is accepted. The results of the average rate of return (ARR) method are 99% greater than the minimum ARR of 50%, so the investment is accepted. The result of the net present value (NPV) analysis is positive, which is Rp. 39,396,778, so the proposed business investment is accepted. The results of the analysis of the Profitability Index (PI) of 1.23> 1, the proposed business investment is accepted, and the results of the Internal Rate Of Return (IRR) analysis of 50%> the desired rate of return, the proposed business investment is accepted.